Aesthetic Anxiety in the Novel Azazel by Youssef Ziedan: An Analytical Aesthetic Approach (Journal of Hama University, 2026)
This study focuses on analyzing the manifestations of aesthetic anxiety in Azazel, the novel by Youssef Ziedan, Although the narrative celebrates beauty, it does so within a fraught context where the psychological intersects with the spiritual, and the symbolic blends with the social, The analysis centers on the character of the monk Hypa, who experiences a continuous inner conflict between his innate attraction to sensual beauty and his entrenchment in a religious structure that demonizes beauty and associates it with sin, By tracing this conflict, aesthetic anxiety emerges as an interpretive condition that transcends the binary of the permissible and the forbidden, raising existential questions about the meaning and limits of beauty, This anxiety extends to other characters as well—most notably Octavia, who embodies aesthetic anxiety from a conscious, feminine perspective—and to the spatial setting itself, where Alexandria transforms from a radiant city into a “cemetery of beauty,” symbolizing the collapse of aesthetic and civilizational memory, The study adopts a psycho-aesthetic approach, drawing upon the concepts of Freud, Kierkegaard, Marcuse, and Blanchot to deconstruct the structure of anxiety in its relation to freedom, desire, and the sacred, It concludes that Azazel employs beauty as a critical tool that interrogates both self and society, turning narrative into a discourse open to the unknown and the uncertain